2016
DOI: 10.1111/ggi.12762
|View full text |Cite
|
Sign up to set email alerts
|

Association between posterior teeth occlusion and functional dependence among older adults in nursing homes in Japan

Abstract: Posterior teeth occlusion was independently associated with functional dependence among nursing home older residents in Japan. The maintenance and restoration of posterior teeth occlusion might be preventive factors against late-life functional decline. Geriatr Gerontol Int 2017; 17: 622-627.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Based on the number of remaining natural teeth, each subject was assigned to an edentulous group, a group with one to nine teeth, or a group with ≥10 teeth. Posterior teeth occlusion was assessed using the total number of functional tooth units (total FTUs) . The total FTUs were defined as the number of pairs of opposing posterior natural teeth and artificial teeth in bridges, dentures or dental implants, excluding carious teeth with extensive coronal destruction.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the number of remaining natural teeth, each subject was assigned to an edentulous group, a group with one to nine teeth, or a group with ≥10 teeth. Posterior teeth occlusion was assessed using the total number of functional tooth units (total FTUs) . The total FTUs were defined as the number of pairs of opposing posterior natural teeth and artificial teeth in bridges, dentures or dental implants, excluding carious teeth with extensive coronal destruction.…”
Section: Methodsmentioning
confidence: 99%
“…To date, we have only found three studies in the literature that have investigated a relationship between FMUs and Barthel index scores (Genkai et al., ; Kwok et al., ; Takeuchi et al., ). Kwok et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of 234 persons over 60 years of age, resident in the city of Aso, Japan, Takeuchi et al. (Takeuchi et al., ) demonstrated that the number of posterior FMUs was significantly associated with the degree of independence for ADL (Barthel index ≥ 60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All measurements were performed by a single dental hygienist (M.I.). This procedure has been described elsewhere (19,20). As measurement of peak flow rate during induced coughing was challenging with the study participants, an alternative to PCF measurement was needed.…”
Section: Coughing Ability Measurement and Questionnairesmentioning
confidence: 99%